1972
DOI: 10.1063/1.3253104
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature Properties and Decomposition of Inorganic Salts Part 3, Nitrates and Nitrites

Abstract: The literature dealing with the high-temperature behavior of inorganic nitrates and nitrites has been critically reviewed. Values of (G'f-H~98)/T of the reactants and products of the decomposition reactions were calculated and have been tabulated from 298 K up to as high a temperature as possible. Equilibrium constants and partial pressures were tabulated. Auxiliary data on phase transitions and densities have also been included. Qualitative information about the thermal decomposition of the salts is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
1
2

Year Published

1985
1985
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 266 publications
(110 citation statements)
references
References 38 publications
5
102
1
2
Order By: Relevance
“…In agreement with published literature [39][40] , it was found that the decomposition does not occur at standard conditions because the reaction requires a Gibbs free energy (G) of 71.9…”
Section: Decomposition Of Pure Nano2supporting
confidence: 75%
“…In agreement with published literature [39][40] , it was found that the decomposition does not occur at standard conditions because the reaction requires a Gibbs free energy (G) of 71.9…”
Section: Decomposition Of Pure Nano2supporting
confidence: 75%
“…In contrast, nitrate has a better affinity for lithium and decomposes at a higher temperature [37,38]. Thus, we can assume that the higher concentration of lithium in the mesopores and the elevated temperature at the start of the metathesis reaction favourably induced the formation of a surface seed crystals (heterogeneous crystallisation), which grew during the second stage of the stabilisation at 500°C for 5 h. This implies that the surface area and pore volume had a direct impact on the formation of this seed crystal, which could explain why higher water content accelerated crystallisation.…”
Section: Crystallisation Behaviour Upon Thermal Stabilisationmentioning
confidence: 99%
“…No solid transitions are reported. It begins to decompose at about 600 K to give N 3 0 , NO, and NO, (Stern 1972). NO reoxidizes the nitrite to nitrate, producing N2.…”
Section: Thermal Data For Compoundsmentioning
confidence: 99%